Yahudi dalam Al-Qur’an dan Relevansinya Terhadap Konflik Palestina: Analisis Tematik dan Historis - Didik Suprastowo; Lukman Sumarna (Jurnal Teologi Islam, 2026)
This study examines the Qur’anic portrayal of the Jews (Bani Israil) and its relevance to the Palestine–Israel conflict. The research aims to analyze Qur’anic verses concerning Bani Israil through a thematic (maudhu‘i) tafsir approach and to relate them to the historical dynamics of the Palestine–Israel conflict. This study employs a qualitative methodology using thematic and historical-critical approaches, with the Qur’an as the primary source, supported by classical and medieval Qur’anic exegesis as well as modern historical studies. The findings indicate that the Qur’anic critique of Bani Israil is behavioral and moral in nature rather than an ethnic generalization, and that it bears relevance to the practices of Zionist ideology in the context of occupation and oppression of the Palestinian people.